2005
DOI: 10.1007/s00425-005-0137-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of arabinogalactan protein genes in pollen tubes of Arabidopsis thaliana

Abstract: The expression of "classical" arabinogalactan protein genes in pollen tubes of Arabidopsis thaliana was characterized by RT-PCR. Transcripts of Agp6 and Agp11 were consistently found to be more abundant in pollen tubes and seem to be pollen-specific. Transcripts of other AGP genes were also detected in pollen but in lesser amounts and in a non-specific fashion. Two reference genes, ubiquitin-conjugating enzyme 9 and tubulin beta-4 chain, were evaluated and selected for gene expression studies in pollen. Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 34 publications
(40 reference statements)
4
59
1
4
Order By: Relevance
“…The specific labelling of the generative cell was also reported for oilseed rape (Pennell et al, 1991), for Nicotiana tabacum (Li et al, 1995) and for Brassica campestris male gametes (Southworth & Kwiatkowski, 1996). JIM8 and JIM13 do not label the pollen tube wall, which instead is labelled by MAC207 and LM2 (Pereira et al, 2006). These two mAbs are probably related to epitopes in structural AGPs present in several types of plant cell walls.…”
Section: Immunolocalization Of Glycan Epitopesmentioning
confidence: 56%
See 2 more Smart Citations
“…The specific labelling of the generative cell was also reported for oilseed rape (Pennell et al, 1991), for Nicotiana tabacum (Li et al, 1995) and for Brassica campestris male gametes (Southworth & Kwiatkowski, 1996). JIM8 and JIM13 do not label the pollen tube wall, which instead is labelled by MAC207 and LM2 (Pereira et al, 2006). These two mAbs are probably related to epitopes in structural AGPs present in several types of plant cell walls.…”
Section: Immunolocalization Of Glycan Epitopesmentioning
confidence: 56%
“…Following studies of pollen and pistil development in Arabidopsis with anti-AGP monoclonal antibodies (Coimbra et al, 2007;Pereira et al, 2006), it became clear that some AGPs may be suitable as molecular markers for gametophytic cell differentiation. Despite the tissuespecific carbohydrate epitopes of AGPs, these investigations do not allow the study of single AGP gene products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…antibody MAC207, it has been demonstrated that AGP epitopes were localized at the tip of the emerging pollen tube in Arabidopsis (Pereira et al, 2006). Using LM6 antibody, the same results were also found in moss apical cells, suggesting that the localized movement of AGPs from plasma membrane to cell wall is a component of the mechanism of tip growth (Lee et al, 2005).…”
Section: Discussionmentioning
confidence: 75%
“…For the 16 Arabidopsis GPI-AGPs, there are some robust groupings (greater than 70% bootstrap values), but only between pairs of sequences. For example, the pollen-specific AtAGP6 and AtAGP11 (Pereira et al, 2006;Coimbra et al, 2009Coimbra et al, , 2010 A, Protein disorder (PONDR) plots (see "Materials and Methods") for AtAGP6 (At5g14380; left), AtEXT3 (At1g21310; middle), and prolyl-4-hydroxylase (AtP4H1; At2g43080; right) using VL-XT (red), VL3 (green), and VSL2 (blue). PONDR prediction scores above the threshold line (0.5) predict disorder; below the line, they predict order.…”
Section: Resultsmentioning
confidence: 99%